THE IMPACT OF E-LEARNING ON ADOLESCENTS' KNOWLEDGE ABOUT PRE-MARRIAGE SEXUAL BEHAVIOR - Rose Nur Hudhariani; Sa'adah Mujahidah; Nova Astika Sari (Jurnal Smart Kebidanan, 2024)
A Health Office report stated that in 2022, 1.9% of teenagers in the Grobogan Regency became pregnant outside of marriage. These adolescents range in age from 15 to 19. Because neither parents nor teenagers can comprehend it, premarital sexual activity is rarely discussed by either group. Teenagers who engage in sexual activity before marriage have access to a limited number of counselling and advocacy centres. There are a lot of young people who participate in risky sexual behaviour before they get married without being aware of the implications. The study utilized a quantitative quasi-experiment with pre- and post-tests administered to a single group. The investigation was carried out in March and April 2024 in the villages of Karanglangu, Kedungjati District, and Grobogan Regency. There were 72 participants in this study. E-learning was provided to the respondents for a period of six weeks. A paired T-test was the statistical test that was chosen. A P-value of 0.000, which is less than 0.05, was found in the statistical test results. It would appear that this form of education impacts the comprehension of premarital sexual behaviour among adolescents.